Adsorção de átomos alcalinos e halogênios em uma superfície de Grafeno: um estudo de primeiros princípios - Silva, José Júnior Alves da (2008)
Graphene is currently the hottest topic in condensed-matter physics and materials science and was isolated less than four years ago. Graphene layers have been proposed as alternative materials for replacing carbon nanotubes in some applications, due to its easy synthesis and low costs. In order to explore potential applications of those nanostructures in electronic devices, through first principles based on the density functional theory, we studied the interaction between graphene surface and alkaline (Li, Na and K) and halogens (Cl, I and I$_2$ ) atoms. We verified that the adsorption of these atoms on the graphene surface cause significant modifications in the graphene electronic structure. We observed a large charge transfer between the alkaline (halogens) atoms and graphene surface. These charge transfers were found to be 0,65 - 0,85 e- from the alkaline atoms to graphene and 0,37 (0,27) e- from the graphene to chlorine (iodine) atoms. The alkaline atoms presented a larger stability on the center of one of the graphene hexagons, presenting binding energy in the range -1, 47 and -1, 03 eV, where the order of intensity is given by Li > K > Na. This predisposition for a specific site was not observed for the twostudied halogens. The chlorine atom present the larger stability when adsorbed on a top atom of the graphene surface with binding energy about 0, 98 eV, however this behavior was not be seen in the iodine atom case where equivalent binding energies for all the studied sites were found to be about 0,42 eV. The I2 molecule also does not present predilection for a specific site on the graphene surface, however it showed more stable when adsorbed with its axis perpendicular to the graphene surface plane.